Molecular biology of Ganoderma pathogenicity and diagnosis in coconut seedlings - Kandan, A; Radjacommare, R; Ramanathan, A; Raguchander, T; Balasubramanian, P; Samiyappan, R (Folia microbiologica, 2009)
The pathogenicity of Ganoderma boninense was tested on coconut seedlings under greenhouse conditions and infection confirmed by using immunological and molecular diagnostic tools. Desiccation of older leaves and the emergence of sporophores were observed from pathogen-inoculated seedlings, whereas a control seedling does not show any pathogenic symptoms. Mature sporophores were formed within 10-13 weeks after inoculation. Polyclonal antibodies raised against mycelial proteins of Ganoderma were used for detection of Ganoderma in infected field palm and seedlings through indirect enzyme-linked immunosorbent assay technique. We adopted dot-immunobinding assay for the detection of Ganoderma from greenhouse and field samples. Under nucleic-acid-based diagnosis, G. boninense (167 bp) was detected from artificially inoculated seedlings and infected field palms by polymerase chain reaction. Apart from these, histopathological studies also support the Ganoderma pathogenicity in coconut seedlings. The pathogenicity test and combination of all the three diagnostic methods for Ganoderma could be highly reliable, rapid, sensitive and effective screening of resistance in planting material in the future.
Keywords: Virulence; Cocos; mezerníky ribozomální DNA; Immunoassay; DNA fungální; virulence; DNA, Ribosomal Spacer; nemoci rostlin; Ganoderma; DNA, Fungal; semenáček; Seedlings; imunoanalýza; polymerázová řetězová reakce; Polymerase Chain Reaction; Plant Diseases